Rhinophyma Treatment by Copper Vapor Laser With the Computerized Scanner - Ponomarev, Igor V.; Topchiy, Sergey B.; Klyuchareva, Svetlana V.; Pushkareva, Alexandra E. (Journal of Lasers in Medical Sciences, 2019)
Introduction: Rhinophyma is recognized as a common and severe skin disease manifested as progressive thickening of the nasal skin due to hypertrophy of the soft tissue. The most severe complication of rhinophyma is telangiectasis. So far the pathogenetic approach for the treatment of rhinophyma should be based on the removal of the dysplastic vessels to provide the appropriate revascularization of the involved skin area. Case Report: This study presented the experience of the treatment of rhinophyma with the copper vapor laser (CVL) designed with the computerized scanner device. A 52-year-old elderly Caucasian male patient with typical clinical signs of rhinophyma was successfully managed during three sessions of CVL treatment. CVL emits light with a wavelength of 578 nm, exposure time of 0.2 seconds. The settings used for the CVL in scanner mode were set at 1.2 W. The scanner device has a hexagonal frame with a maximum width of 12 mm with the distance of 1 mm between centers of laser spots. The CVL treatment resulted in a restoration of the natural appearance of the nose without side effect during 18 months after treatment. Conclusion: The described clinical case demonstrates excellent results of the management of rhinophyma by means of the scanned CVL. CVL treatment was associated with the removal both of dysplastic superficial skin vessels, the solution of the inflammation, decline of the sebum production and the disappearance of the nasal hypertrophy.